Self-regulation of drivers' mobile phone use: The influence of driving context. (October 2019) - Christoph, Michiel; Wesseling, Simone; van Nes, Nicole
Highlights: Drivers regulate visual-manual phone tasks in relation to the driving context. Road type, situation complexity and passenger presence relate to visual-manual task engagement. 25% of visual-manual tasks are initiated while standing still in traffic. Abstract: Mobile phone use while driving is a major concern for traffic safety. Various studies indicate negative effects of distracted driving and recent Naturalistic Driving studies report substantial increase in crash risk of mobile phone use while driving. The increasing level of vehicle automation is likely to further increase phone use behind the wheel, as the automation takes over part of the driving task drivers are likely to experience boredom and feel more confident to get involved in other activities such as phone use. This may further increase the distraction related accidents on our roads. However, the extent to which this further increases depends largely on the drivers' level of self-regulation of risk, the timing of engagement in phone activities in relation to the driving context. The objective of this study was to investigate if drivers self-regulate their mobile phone use, specifically focussed on the visual manual (VM) task which is associated with the largest increase in risk, while driving in relation to different driving contexts. For this study naturalistic driving data was analysed of Dutch car drivers collected in the UDRIVE project. The results show that Dutch drivers spent over 9% of all driving time engaging in mobile phone related tasks, including calling and VM tasks such as texting. Drivers used their mobile phone significantly less when a passenger was present. Also, significantly more VM tasks were initiated during standstill than for the other speed categories. In addition, on rural roads relatively less time was spent on VM tasks and on highways relatively more time was spent on VM tasks. Overall the results show that the driving context seems to influence the initiation and involvement in VM tasks, which is an indication that drivers self-regulate this behaviour.